Neural stem cells for spinal cord repair - Sandner, Beatrice; Prang, Peter; Rivera, Francisco J.; Blesch, Armin; Weidner, Norbert (Cell & tissue research, 2012)
Spinal cord injury (SCI) causes the irreversible loss of spinal cord parenchyma including astroglia, oligodendroglia and neurons. In particular, severe injuries can lead to an almost complete neural cell loss at the lesion site and structural and functional recovery might only be accomplished by appropriate cell and tissue replacement. Stem cells have the capacity to differentiate into all relevant neural cell types necessary to replace degenerated spinal cord tissue and can now be obtained from virtually any stage of development. Within the last two decades, many in vivo studies in small animal models of SCI have demonstrated that stem cell transplantation can promote morphological and, in some cases, functional recovery via various mechanisms including remyelination, axon growth and regeneration, or neuronal replacement. However, only two well-documented neural-stem-cell-based transplantation strategies have moved to phase I clinical trials to date. This review aims to provide an overview about the current status of preclinical and clinical neural stem cell transplantation and discusses future perspectives in the field.